Pemetaan Endapan Mineral Teralterasi Hidrotermal Menggunakan Analisis Citra Landsat 8 di Sekitar Gunung Api Bur Ni Geureudong, Kabupaten Bener Meriah, Aceh - Nazli Ismail; Nela Wirja; Deviyani R. Putri; Muhammad Nanda; Faisal Faisal (Jurnal Rekayasa Elektrika, 2020)
Vegetation area and altered mineral by hydrothermal mapping using Landsat 8 satellite data has been done at Bur Ni Geurudong Volcano, Bener Meriah Regency, Aceh Province. Bands 5 and 4 data were used for Normalized Different Vegetation Index (NDVI) transformation technique. Band composition ratio of 6/5 and 6/7 were used for band ratio technique to interprete ferric oxide and clay minerals. The results show moderate (0.2-0.5) distribution of vegetation density found at Wih Pesam and Pante Raya Barat. The high density (0.50-0.88) vegetation areas are found at Silih Nara and Pinto Rime Gayo. The maximum distribution (1.98-2.23) of ferric oxide minerals found at Bur Ni Telong and few at Pinto Rime Gayo with sulfur content manifestation. This mineral is also founded on Silinara manifestation area. Maximum (2.33-8.88) distribution of clay mineral was found at Bur Ni Geureudong Volcano, few seen at Bur Ni Telong area. Based on the results, the Landsat 8 satellite imagery is effectively used for mapping of ferric oxide and clay minerals. Mapping of ferric oxide and clay minerals rovide information about the types of minerals that exist in Bur Ni Geurudong Volcano as a preliminary information about the types of geothermal reservoir rocks in the region.